Structural basis for the 3'-5' exonuclease activity of Escherichia coli DNA polymerase I: a two metal ion mechanism. - Beese, L S (1991)
The refined crystal structures of the large proteolytic fragment (Klenow fragment) of Escherichia coli DNA polymerase I and its complexes with a deoxynucleoside monophosphate product and a single-stranded DNA substrate offer a detailed picture of an editing 3'-5' exonuclease active site. The structures of these complexes have been refined to R-factors of 0.18 and 0.19 at 2.6 and 3.1 A resolution respectively. The complex with a thymidine tetranucleotide complex shows numerous hydrophobic and hydrogen-bonding interactions between the protein and an extended tetranucleotide that account for the ability of this enzyme to denature four nucleotides at the 3' end of duplex DNA. The structures of these complexes provide details that support and extend a proposed two metal ion mechanism for the 3'-5' editing exonuclease reaction that may be general for a large family of phosphoryltransfer enzymes. A nucleophilic attack on the phosphorous atom of the terminal nucleotide is postulated to be carried out by a hydroxide ion that is activated by one divalent metal, while the expected pentacoordinate transition state and the leaving oxyanion are stabilized by a second divalent metal ion that is 3.9 A from the first. Virtually all aspects of the pretransition state substrate complex are directly seen in the structures, and only very small changes in the positions of phosphate atoms are required to form the transition state.